2014
DOI: 10.1053/j.gastro.2013.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Responses in Enteric Glia Are Mediated by Connexin-43 Hemichannels and Modulate Colonic Transit in Mice

Abstract: Background & Aims In the enteric nervous system, neurotransmitters initiate changes in Ca2+ (Ca2+ responses) in glia, but it is not clear how this process affects intestinal function. We investigated whether Ca2+-mediated responses in enteric glial are required to maintain gastrointestinal function. Methods We used in situ Ca2+ imaging to monitor glial Ca2+ responses, which were manipulated with pharmacologic agents or via glia-specific disruption of the gene encoding connexin-43 (Cx43) (hGFAP::creERT2+/−/Cx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
227
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(244 citation statements)
references
References 51 publications
8
227
3
Order By: Relevance
“…For example, Jain et al used hM3Dq transgenic mice to demonstrate that Gq-GPCR signaling in pancreatic β cells led to activation of ERK1/2 and IRS2 signaling; this activation led to markedly improved β cell function (55). Recent studies where Gfap-hM3Dq was used to activate enteric glia revealed novel mechanisms of glial regulation of gastrointestinal functions (15,56). In combination with pharmacological agents and by using in situ models, Gfap-hM3Dq mice serve as a useful model to study GFAP + glial functions in complex tissues and in intact animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Jain et al used hM3Dq transgenic mice to demonstrate that Gq-GPCR signaling in pancreatic β cells led to activation of ERK1/2 and IRS2 signaling; this activation led to markedly improved β cell function (55). Recent studies where Gfap-hM3Dq was used to activate enteric glia revealed novel mechanisms of glial regulation of gastrointestinal functions (15,56). In combination with pharmacological agents and by using in situ models, Gfap-hM3Dq mice serve as a useful model to study GFAP + glial functions in complex tissues and in intact animals.…”
Section: Discussionmentioning
confidence: 99%
“…Although SNA is mainly considered a product of integration by neuronal networks, recent evidence suggests that Gq G protein-coupled receptor (Gq-GPCR) activation in glial fibrillary acidic protein-expressing (GFAP + ) glia (CNS astrocytes and non-myelinating peripheral glia) also contributes to homeostatic control of blood gases (11)(12)(13) and gastrointestinal motility (14,15) via modulation of local neuronal activity. Recently, we showed that selective activation of Gq-GPCR signaling in GFAP + glia in vivo led to acute changes in autonomic functions, including increases in heart rate and blood pressure (16).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that enteric glial cells tune in to neuronal activity 108,109 and take part in ENS signaling that underlies colonic motility. 110,111 Also, our understanding of myogenic and other mesenchymal control elements present in the gut wall, has improved based on imaging results. For example, recent reports show that interstitial cells of Cajal can operate independently from enteric neurons to control segmentation motor activity, 112 and need the Ca 2+ -activated Cl − channel Ano1 to coordinate slow waves in the smooth muscle.…”
Section: Live Imaging Of Cellular Activity In the Adult Gutmentioning
confidence: 99%
“…In the CNS, GFAP + astrocytes reside in close proximity to active synapses [4] , and regulate neuronal activity [5] and signal processing [6] in an activity-dependent and circuit-specific manner [7] . Recent studies on enteric glia revealed novel mechanisms of GFAP + glial regulation of gastrointestinal functions [8,9] , suggesting powerful neuromodulatory potential of GFAP + glia in the peripheral nervous system. We began by testing the role of GFAP + glia in the SNS in vivo.…”
Section: Introductionmentioning
confidence: 99%